HUBUNGAN KELINCAHAN DENGAN KECEPATAN DRIBBLING PEMAIN SEPAKBOLA TIM SMN 1 SEDINGINAN KECAMATAN TANAH PUTIH - ', Faisal; ', Saripin; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the low-speed dribbling soccer player on the team SMAN 1 Sedinginan. This problem can be seen from the observation of researcher during a match, it is suspected because of the agility of soccer players team SMAN 1 Sedinginan. Therefore, the purpose of this study was to determine whether there is a corelation between agility with speed dribbling soccer players Tim SMAN 1 Sedinginan. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As independent variables (X1) is agility while the dependent variable (Y) is the speed dribbling. This research data obtained from the test results using a dodging run agility test, and speed soccer dribbling test. The sample in this research are male students of class X-XI numbered 30 people (total sampling). Based on the research results can be concluded as follows: